First record of marine wood borer (Mollusca: Teredinidae) Dicyathifer mannii Wright (1866) in Sabah, Malaysia, with detailed measurement metrics - Loo, An zHEN; Chen, Cheng Ann; Khairul Adha A. Rahim; Farah Diba (Penerbit UMS, 2019)
The present study describes the new record of Dicyathifer mannii under the family Teredinidae Rafinesque, 1815. Sampling was conducted in the mangrove area of Kuala Penyu and sample was collected from dead wood debris. The pallets of Dicyathifer is half-conical in shape and 8mm in length. The cone measured 3.9mm in length and 3.6mm in width. The cavity is 1.2mm deep; the curve of the opening on the cone is about 98% of the depth of the cone. Inside the cone cavity, from the center, a ridge with rib-like feature runs down the length of the cavity. Only one species of Dicyathifer is recorded and the present species is the first new record described in Malaysia with some additional measurement metrics for future taxonomic identification purposes.